1990
DOI: 10.1016/0014-5793(90)80274-m
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of 2‐phosphoglycerate by cytotoxin B of Clostridium difficile

Abstract: Cytotoxin B of C. difficile was highly purified by selective ammonium sulfate precipitation, Biogel A5m chromatography, phenyl boronate hydrophobic interaction chromatography and ultracentrifugation. The final cytotoxic product had a specific activity of 7.8 × 108 protein and showed a single protein band with an estimated molecular weight of 163000 when subjected to SDS‐PAGE. Immunoelectrophoresis of the final product showed a single precipitin arc. The addition of cytotoxin B to imidazole‐HCl buffer (pH 7.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Further purification of pooled fractions containing cytotoxicity on a Sephacryl $300 gel filtration column also showed co-elution of toxicity and enolase activity. This is in agreement with literature where it has been reported that enolase activity copurifies with toxin B in a wide variety of purification methods including (NH4)2SO4 precipitation, Biogel A5m gelfiltration, phenylboronate column chromatography, ultracentrifugation [4], FPLC anion exchange [7], and DEAESepharose ion-exchange chromatography. Neutralization of cytotoxicity by C sordellii antitoxin did not result in inhibition of enolase activity.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Further purification of pooled fractions containing cytotoxicity on a Sephacryl $300 gel filtration column also showed co-elution of toxicity and enolase activity. This is in agreement with literature where it has been reported that enolase activity copurifies with toxin B in a wide variety of purification methods including (NH4)2SO4 precipitation, Biogel A5m gelfiltration, phenylboronate column chromatography, ultracentrifugation [4], FPLC anion exchange [7], and DEAESepharose ion-exchange chromatography. Neutralization of cytotoxicity by C sordellii antitoxin did not result in inhibition of enolase activity.…”
supporting
confidence: 93%
“…The toxin B gene has been sequenced [2,3]. Knoop et al [4] showed that toxin B has enolase activity as measured by degradation of 2-phosphoglycerate. Here we show that toxin B does not have enolase activity.…”
Section: Received 30 October 1992mentioning
confidence: 99%
See 1 more Smart Citation
“…These functions include its identi ed role as Hsp48, a heat shock protein in Saccharomyces cerevisiae, its structural role in crystallin formation in the turtle eye lens and its possible identity as cytotoxin B of Clostridium dif cile, in which it acts to disrupt the micro lament cytoskeleton by inhibiting adenosine diphosphate (ADP)-ribosylation of the guanosine 5 0 -triphosphate (GTP)-binding protein Rho [1][2][3][4][5][6]. It exhibits additional, nonglycolytic functions in some organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The reported molecular weights for native toxins A and B have ranged from 440,000 to 600,000 and 107,000 to 550,000, respectively (10,14,15,129,130,148,235,259,265,290 (234) reported that toxin A had a native molecular weight of 52,000 and could be dissociated with 1% sodium VOL. 6,1993 on April 27, 2019 by guest http://cmr.asm.org/ Downloaded from dodecyl sulfate into two subunits with molecular weights of 41,500 and 16,000.…”
Section: Introductionmentioning
confidence: 99%